2018
DOI: 10.1016/j.conbuildmat.2017.12.142
|View full text |Cite
|
Sign up to set email alerts
|

Influence of loading and cracks on carbonation of RC elements made of different concrete types

Abstract: Accurate prediction of the carbonation rate of a particular concrete is important for the correct assessment of both durability and environmental impact of reinforced concrete (RC) structures. Applied loading and caused by it concrete cracking are major factors affecting the carbonation, which so far have received little attention of researchers, especially this concerns 'green' concretes, i.e. concretes in which Portland cement (PC) is partially replaced by supplementary cementitious materials such as fly ash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 36 publications
(46 reference statements)
1
29
0
Order By: Relevance
“…However, RC elements in real structures are under loading but only a few studies have investigated carbonation of concrete in a stressed state [30][31][32][33][34]. These studies indicated a significant influence of stresses, especially tensile stresses, on the rate of carbonation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, RC elements in real structures are under loading but only a few studies have investigated carbonation of concrete in a stressed state [30][31][32][33][34]. These studies indicated a significant influence of stresses, especially tensile stresses, on the rate of carbonation.…”
Section: Introductionmentioning
confidence: 99%
“…Even fewer studies have addressed the influence of loading and cracking on carbonation of 'green' concretes [33,34]. Wang et al [33] conducted tests to examine the effects of compressive and tensile stresses and high exposure temperature on the carbonation resistance of PC and FA concretes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing RC buildings ordinary have some cracks. These expand air permeation and water penetration (D. Breysee et al,), which cause irregular carbonation (Xiao-Hui et al, 2018), and rebar corrosions rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…Well-designed classical retrofitting interventions can improve the seismic strength of the masonry macro-element but, on the other hand, they can change the collapse mode, inhibiting the simple overturning mechanism and then modifying the structural behaviour of the entire structure. As an example [35][36][37][38]: the steel chains and belting, increasing the out-of-plane wall strength, can inhibit the overturning kinematism transforming it into vertical bending; external steel reinforcement technique, due to their large stiffness, tends to localize seismic stresses; the mesh reinforcement, as well as the FRP rehabilitation systems, significantly improve both ductility and in-plane capacity of the element, but the out-of-plane capacity is guaranteed only if adequate connections are introduced and in this case the seismic behaviour turns into a bending out of plane.In the present paper, a novel retrofitting technique, taking the cue from a typology of intervention frequently used in the past and nowadays recovered, is analysed: the vertical FRP rebars. The adoption of this retrofitting methodology in several case studies seems to confirm its effectiveness.…”
mentioning
confidence: 99%